Phylogenetic Study of Bufonidae (Amphibia: Anura) from Sumatera and Asia Based on Cytochrome B Gene - Djong Hon Tjong; Dewi Imelda Roesma; Silvia Indra (Journal of Tropical Life Science, 2021)
Bufonidae is widely distributed amphibian family around the world, including Indonesia (Sumatra) and Asia. Sumatra is an island which has separated because of sea level increase and create gene flows barrier for amphibian in Sumatra and Asia. The purpose of this research is to analyse Bufonidae phylogenetic which exist in several locations in Sumatra and Asia based on gene cytochrome b analysis. Samples were collected from six localities in West Sumatra. DNA extraction and amplification has been done in Genetics and Cell Biology Laboratory, Andalas University, whereas DNA sequencing were analyzed at MacroGen USA DNA Sequencing Laboratory, South Korea. About 14 tissue samples of Bufonidae from West Sumatra has been analyzed. The relationship of Bufonidae phylogenetics in Sumatra and Asia were divided into three main clusters. Duttaphrynus melanostictus in Sumatra is closer to Duttaphrynus melanostictus from India with 0,3-0,5% sequence divergence and it is a group of paraphyletic with Duttaphrynus melanostictus from Vietnam, Taiwan, and China.